1976
DOI: 10.1093/ajcp/65.6.929
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Electronmicroscopic Characteristics of a Case of Immunoblastic Lymphadenopathy

Abstract: A new disease entity of the lymphoid system has recently been reported by Lukes and Tindle as immunoblastic lymphadenopathy and by Frizzera and associates as angioimmunoblastic lymphadenopathy with dysproteinemia. Reported herein are cytologic, histologic, ultrastructural and immunologic studies of several tissues of a patient with this disorder. In addition to confirming the previous observations that the main cellular constituents in the affected tissue consist of immunoblast, plasmacytoid lymphocytes and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

1977
1977
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(20 citation statements)
references
References 0 publications
4
14
0
2
Order By: Relevance
“…Previous studies have demonstrated spontaneous Ig production by MNC from AILD patients (8). Our findings are consistent with those reports in that AILD T cells plus AILD B cells led to proliferation and Ig production (7,10,11).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have demonstrated spontaneous Ig production by MNC from AILD patients (8). Our findings are consistent with those reports in that AILD T cells plus AILD B cells led to proliferation and Ig production (7,10,11).…”
Section: Discussionsupporting
confidence: 93%
“…Although the clinical and pathologic features of patients with AILD are becoming better understood, there is considerable confusion regarding the cellular abnormalities that underlie this disorder (7)(8)(9)(10)(11)(12)(13). Most patients have an abnormal composition of their peripheral blood leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…As has been pointed out by Moore and co-workers (1976) , the possibility of a viral cause cannot be excluded. It is noteworthy that rubella infection has preceeded the onset of immunoblastic lymphadenopathy by 3 months in a case reported by Palutke et al (1976). Of another interest is the case described by Schlutz and Yunis (1975).…”
Section: Discussionmentioning
confidence: 93%
“…Palutke et a1. 17 however, considered the interstitial eosinophilic material to be composed of cellular debris. The plethora of small blood vessels, which is a characteristic feature of this lesion, may reflect the action of lymphocyteinduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%